Impact of subsidies in an agricultural exploitation of medium size from vegetable sector - Daniela-Elena Şurcǎ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Exploitations of small and medium size plays an important role in Romanian agriculture, which are numerous, representing a significant percentage of the total number of those receiving subsidies. In this regard a case study drawn up on a farm representative of mid-size indicates the significant contribution has subsidization and which currently makes a clear separation between profit and loss for the Romanian farmer.
Keywords: Q12; 330; subventions; agricultural exploitation; technical and economic indicators